Economic spatial structure of China's urban agglomerations: Regional differences, distribution dynamics, and convergence. (December 2022) - Liu, Kai; Xue, Yuting; Chen, Zhongfei; Miao, Yi; Shi, Jialu
Highlights: Economic spatial structure has the polycentric characteristic. Economic spatial structure shows significant regional differences. The intensity of transvariation is a major contributor to regional differences. There is a polarization characteristic concerning economic spatial structure. Absolute and conditional β-convergences both have emerged. Abstract: The economic spatial structure (ESS) is of paramount importance to the robust development of urban agglomerations (UAs), which requires further and deeper inquiry. This paper measures the ESS of UAs using the Herfindahl-Hirschman Index (HHI), examines its regional differences by Dagum's decomposition of the Gini coefficient, explores its distribution dynamics through kernel density estimation (KDE), and tests the convergence with the coefficient of variation (CV) and regression models. According to the results, the HHI of each UA was at a low level, showing a prominent polycentric structure composed of rising, stable, and low-level types. There were significant regional differences within and between UAs concerning ESS, and the overall difference displayed an N-shaped trend of "rising-falling-rising", with the intensity of transvariation as a major contributor. The center and change interval of the overall distribution curve of UAs' ESS tended to move rightward slightly over time, which was characterized by polarization. There were absolute and conditional β-convergences within and between UAs at different levels and as a whole.